Local flap for open fracture grade IIIB tibia - Mohd Yusof, Nazri; Zulkifly, Ahmad Hafiz; Zakaria@Mohamad, Zamzuri; Che Ahmad, Aminudin (2006)
Background The tibia can easily be exposed following trauma because of its subcutaneous location. The expose bone needs to be covered to prevent it from becoming desiccated and infected. Local flap are one of the options to solve this problem. It is quite easy to perform and does not required any micro surgical expertise and instrument. Objective: To review the short term outcome of local flap for open grade IIB tibia fracture Methodology: A case series of patients with grade IIIB open tibial fracture treated in Hopsital Tengku Ampuan Afzan from 2002 to 2006. The operation and follow up was done by the first author. Results: There were fasciocutaneous flap, 5 muscles flap, 1 muscles combined fasciocutaneous flap and 4 musculocutaneous flap. Eleven flaps healed unevenly. There was superficial flap necrosis, 1 wound breakdown and 1 partial skin graft failure. Conclusion: Local flap is an option for orthopaedic surgeon to cover selected soft tissue defect in the leg. Careful assessment of injury, surgical planning and adhering to surgical principle will ensure good outcome for the patient.